2019
DOI: 10.7759/cureus.5352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexmedetomidine on Levobupivacaine and Ropivacaine in Fascia Iliaca Block for Trochanteric Fractures Treated by Proximal Femoral Nail – A Randomized Trial

Abstract: Background: Fascia iliaca block (FIB) is an established procedure for postoperative pain relief in femur fracture surgeries. Dexmedetomidine was found to be a useful additive to local anesthetics (LA) for peripheral nerve blocks resulting in a prolonged anesthetic effect. We evaluated the impact of the addition of dexmedetomidine to an equal concentration of levobupivacaine and ropivacaine for FIB. Methods: The present study is a double-blind, randomized trial conducted on 60 patients in the age group 18-70 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…In our centre, SFICB are performed using 40 ml of ropivacaine 0.375% with 5 mg of dexamethasone added as an intravenous additive. The estimated duration of effect of this block differs between studies, but is in the range of 12 to 24 hours [23][24][25] . Therefore, the absence of a significant difference in PCIA morphine use between 24 and 48 hours postoperatively was to be expected.…”
Section: Discussionmentioning
confidence: 94%
“…In our centre, SFICB are performed using 40 ml of ropivacaine 0.375% with 5 mg of dexamethasone added as an intravenous additive. The estimated duration of effect of this block differs between studies, but is in the range of 12 to 24 hours [23][24][25] . Therefore, the absence of a significant difference in PCIA morphine use between 24 and 48 hours postoperatively was to be expected.…”
Section: Discussionmentioning
confidence: 94%
“…Mean of time for first rescue analgesia : The mean Time for First Rescue Analgesia in the Group LD was {290.29 ± 29.28} considerably higher than in the Group RD {197.65 ± 26.75}. Sriramka et al ( 23 ) observed that duration of analgesia was found to be slightly longer in group LD (955.3 ± 114.5 minutes) than in group RD patients (894.6 ± 91.3) with p = 0.027, with a higher rescue analgesia requirement in RD group.…”
Section: Discussionmentioning
confidence: 96%